Dendritic growth with the six-fold symmetry: Theoretical predictions and experimental verification. (September 2017) - Alexandrov, D.V.; Galenko, P.K.
Abstract: A free dendrite growing in a pure substance is considered with the interfacial effect of anisotropy and convective flow. A stable mode of dendritic growth with the six-fold crystal symmetry is studied using the solvability theory. We demonstrate that the obtained selection criterion for a stable mode of dendritic growth is a function of surface energy stiffness, arbitrary values of Péclet numbers and convective flow intensity. To predict the dendrite tip velocity V and its tip radius R a model of dendrite growth with the six-fold symmetry is formulated. We show that the model equations can be reduced to the growth kinetics with the low Péclet numbers, which exhibit the explicit relationships "tip velocity - undercooling". The model predictions are compared with experimental data on ice dendrites grown from pure undercooled water on board of the International Space Station (under microgravitational conditions, μ g ) and on the Ground (under terrestrial conditions, 1 g). Abstract : Highlights: Selection criterion for dendritic growth with six-fold symmetry is derived. Theoretical model predicts the dendrite velocity and tip radius. Test of the model in comparison with experimental data on ice dendrites is given.